2010
DOI: 10.2109/jcersj2.118.909
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of Cymbal piezoelectric transducers for harvesting energy from asphalt pavement

Abstract: The purpose of this paper is to design a Cymbal for harvesting energy from asphalt pavement. Asphalt pavement is used popular on road. Part of the energies in the pavement caused by vehicle and gravity can be harvested by piezoelectric transducers. Cymbal is selected to harvest energy from asphalt pavement because of its low cost, high reliability and reasonable efficiency. The efficiency and coupling effects with pavement of Cymbals with various sizes are discussed through finite element analysis (FEA). The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(81 citation statements)
references
References 10 publications
0
64
0
1
Order By: Relevance
“…Furthermore, the potential pyroelectric effect is not considered. Zhao et al (2010) proposed a cymbal-shaped PZT-based energy harvester and analyzed its coupling with asphalt pavement structure using a finite element model. PVDF-based energy harvesters have also been investigated that convert ambient vibration into electricity (Chen, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the potential pyroelectric effect is not considered. Zhao et al (2010) proposed a cymbal-shaped PZT-based energy harvester and analyzed its coupling with asphalt pavement structure using a finite element model. PVDF-based energy harvesters have also been investigated that convert ambient vibration into electricity (Chen, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al [26] studied the efficiency and coupling effects on various dimensions of cymbal PEH from the pavement caused by vehicle and gravity via finite element analysis (FEA). Considering the storage electric energy, cost, bonding between end steel cap and PZT, and pavement surface displacement, the optimum one was with total diameter (32 mm), cavity base diameter (22 mm), end cap top diameter (10 mm), cap steel thickness (0.3 mm), cavity height (2 mm), and PZT thickness (2 mm).…”
Section: Cymbal Structurementioning
confidence: 99%
“…Vibration amplitude and frequency not only relate with the material structure of the road, but also with the traffic load and speed; so the vibration amplitude and frequency for road energy harvesting is in a wide range. It has been shown that the resonant frequency of urban roads with asphalt pavement was about 20Hz [23,24]. For the bridge condition monitoring, the main resonant frequencies of the bridge deck were identified in the range from 0-50Hz by installing energy harvester on the girders and the pipe fixed on the girders under a bridge in France, where the power spectral densities have the peak values at the frequencies around 14.5Hz [25].…”
Section: Design Of the Cantilever Beammentioning
confidence: 99%